FORMULASI SEDIAAN SABUN PADAT FRAKSI ETIL ASETAT DAUN JERUK PURUT (Citrus hystrix) SEBAGAI ANTIMIKROBA - Kalalo, Tasya Kensy; Yamlean, Paulina V.Y; Abdullah, Surya Sumantri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
The kaffir lime plant (Citrus hystrix) contains flavonoids, alkaloids, saponins, steroids, terpenoids, and tannins, which have antimicrobial activity. This study aims to determine whether the solid soap formulation of the ethyl acetate fraction of kaffir lime leaves possesses antimicrobial activity and to find the optimum concentration for this effect. The research employed an experimental laboratory method. Extraction and fractionation were conducted using various solvents, followed by antimicrobial activity testing. The results showed that the ethyl acetate fraction exhibited the strongest antibacterial activity with an inhibition zone of 16 mm against Staphylococcus aureus, while there was no inhibition zone against Candida albicans. Solid soap formulations were made with concentration variations of 0%, 1%, 3%, and 5%, all meeting physical evaluation requirements. Antimicrobial testing of the solid soap against Staphylococcus aureus showed the highest antibacterial activity with an inhibition zone of 10.5 mm at a 5% concentration. It can be concluded that all solid soap formulations of the ethyl acetate fraction of kaffir lime leaves demonstrated antimicrobial activity against Staphylococcus aureus, with the highest activity at a 5% concentration, resulting in a 10.5 mm inhibition zone.